A Socio-Technical Windows 11 Hardening Framework Integrating Ferret-Windows and CIS Benchmarks - Prasetyo Adi Wibowo Putro; Ray Novita Yasa Yasa; Mochammad Latief Reswandana Musonip; Dimas Nugroho Putro; Agry Zharfa (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2026)
The high level of vulnerability in the Windows operating system requires implementing a hardening strategy that focuses not only on technical security but also on end-user convenience. This study, using a Design Science Research (DSR) methodology, aims to design and evaluate a Windows-based host security configuration by applying 35 parameters developed by integrating the Ferret-Windows open-source tool and the Microsoft Windows 11 Benchmark CIS standard. The research method includes a descriptive study to analyze the effectiveness of the tool and its parameter formulation, and a prescriptive study to formulate a combined configuration. The evaluation was carried out through functional testing and usability measurements using the System Usability Scale (SUS) instrument for 31 end-users (e.g., staff and students) in a public institution context, using the System Usability Scale (SUS) instrument on a standardized test laptop. The results showed that the configured system obtained an average SUS score of 73.63, which falls within the